THE ROLE OF STORYTELLING AND GAMES IN TEACHING ENGLISH TO YOUNGER LEARNERS: A COMPREHENSIVE ANALYSIS - Aliboyeva Nilufar Akhror qizi; Consultant: Xolmirzayev X. D. Prof (Modern American Journals, 2025)
Storytelling and educational games play a key role in modern English as a Foreign Language (EFL) teaching, especially among younger learners, promoting language acquisition, cognitive engagement, and motivation. Research in language pedagogy and educational psychology confirms their effectiveness in developing fluency, memorization, and comprehension. This article provides an overview of theoretical models, empirical research, and quantitative analysis of data confirming their pedagogical significance. The findings highlight the importance of integrating narrative and playful learning into English language learning programmes, enabling contextual and interactive language acquisition.
Keywords: Storytelling, Educational Games, English Language Teaching, Student Engagement, Cognitive Development, Gamification, Fluency, Language Memorization